Modified hydroxyapatite bone repair material as well as preparation method and application thereof
By modifying hydroxyapatite bone repair material, combining demineralized bone matrix powder and wrapping PEG-GA-COO-NHS liposomes, the problems of thermal damage, non-degradability and insufficient biological activity of existing bone cement materials in bone defect repair are solved, and efficient bone repair and regeneration are achieved.
Patent Information
- Application Number
- CN202510010870.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
AI Technical Summary
Existing bone cement materials generate a large amount of heat energy during polymerization, which may damage the surrounding important organs. The materials are non-degradable and have no biological activity, and have problems such as poor anti-collapse and poor ability to induce bone regeneration, which limits their application in bone defect repair.
Modified hydroxyapatite bone repair material, which contains carboxy modified polyethylene glycol modified hydroxyapatite, demineralized bone matrix powder and liposomes wrapped in polyethylene glycol succinic anhydride succinimide ester, is covalently linked by amide bonds to form bone repair material with anti-collapse, high compressive strength, anti-infection and biocompatible.
This material is injectable, has controllable curing time, has anti-collapse, high compressive strength, good anti-infection and biocompatible, and can effectively guide bone tissue regeneration, solving the shortcomings of existing bone cement materials in bone defect repair.
Smart Images

Figure CN119792633A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biological tissue engineering materials, and specifically relates to a modified hydroxyapatite bone repair material and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Bone defects are one of the most common clinical orthopedic diseases, which can be caused by infection, trauma, tumors and congenital diseases. Most of them cannot heal on their own and require bone transplantation. With the aging of the population, bones have become the second largest transplanted tissue in the world. With the development of minimally invasive surgical techniques, injectable bone repair materials have become a kind of bone tissue regeneration and repair material urgently needed in clinical practice. Injectable bone materials widely used in clinical practice include polymethylmethacrylate (PMMA) bone cement and calcium phosphate cement (CPC), which are usually composed of a solid phase and a liquid phase. The slurry formed by the full mixing of the solid phase and the liquid phase can be solidified in situ in the body after being injected into the human body. The solidified block has a certain mechanical strength, thereby providing support for the bone defect site to maintain bone stability.
[0004] The solid phase prepolymer of PMMA bone cement is mainly PMMA and initiator (benzoyl peroxide), and the liquid phase contains monomer methyl methacrylate and chemical activator (catalyst dimethyl para-toluidine). It has good plasticity and vertebral shaping ability. After injection into the vertebral body, it can restore the strength and stiffness of the affected vertebra, enhance the biomechanical stability of the affected vertebra, relieve pain, and enable patients to get out of bed and move around as soon as possible to avoid related complications caused by long-term bed rest. However, PMMA will generate a lot of heat energy during polymerization, which will cause damage to surrounding important organs, and PMMA monomer is toxic, which will cause changes in the coagulation mechanism after absorption by the human body. At the same time, PMMA is non-degradable and has no biological activity. Long-term presence in the body will cause problems such as loosening of the interface between vertebral cancellous bone and bone cement.
[0005] Calcium phosphate cement (CPC) can solidify spontaneously after being injected into the human body. Compared with PMMA-based cement, it has low heat release during the solidification process, is bioactive, and can undergo specific chemical reactions with bone tissue to promote the adhesion, proliferation, and differentiation of osteoblasts. However, it has problems such as poor injectability, poor anti-collapse, and poor ability to induce bone regeneration.
[0006] The above problems limit the application of bone cement. It is necessary to develop an injectable bone repair material with the following characteristics: (1) anti-infection function. Bone infection is a common complication of bone defects. Bone repair materials with anti-infection function will help reduce bone defect infection and promote bone repair; (2) compression resistance and bending ability. Bones are the supporting scaffolds of the body and have a certain load-bearing capacity. Bone repair materials used for bone defect repair must have compression resistance and bending ability suitable for the body; (3) biosafety and the function of promoting the regeneration of defective bone tissue. Summary of the invention
[0007] In view of the deficiencies of the above-mentioned prior art, the present invention provides a modified hydroxyapatite bone repair material and its preparation method and application. Specifically, the modified hydroxyapatite bone repair material at least comprises hydroxyapatite (NHS-PEG-COO-HA) modified by carboxyl-modified polyethylene glycol (COOH-PEG-COOH), demineralized bone matrix powder (DBM), and liposomes encapsulating polyethylene glycol (PEG)-gallic acid (GA)-succinic anhydride-succinimide ester (NHS ester) (PEG-GA-COO-NHS), and the three are mixed with water and covalently linked by amide bonds. It has been verified by experiments that the modified hydroxyapatite bone repair material has the characteristics of injectability, adjustable curing time, anti-disintegration, strong compressive strength, anti-infection, good biocompatibility, and the performance of guiding bone tissue regeneration. Based on the above research results, the present invention is completed.
[0008] The present invention is achieved through the following technical solutions:
[0009] The first aspect of the present invention provides a modified hydroxyapatite bone repair material, wherein the modified hydroxyapatite bone repair material comprises at least the following raw materials in parts by weight:
[0010] NHS-PEG-COO-HA 5-15 parts, DBM 0.5-3 parts, PEG-GA-COO-NHS-encapsulated liposomes 0.1-1 parts;
[0011] Wherein, the structural formula of the NHS-PEG-COO-HA is:
[0012] n can be 300 to 1200.
[0013] The DBM is prepared by a method comprising: defatting, decalcifying, decellularizing, and removing telopeptide from bones of non-human animals, and drying the bones to obtain the DBM.
[0014] Among them, the structural formula of PEG-GA-COO-NHS is:
[0015]
[0016] n can be 100-400.
[0017] The second aspect of the present invention provides a method for preparing the modified hydroxyapatite bone repair material, the method comprising:
[0018] S1. Preparation of NHS-PEG-COO-HA: COOH-PEG-COOH modified hydroxyapatite (COOH-PEG-HA) was dissolved with NHS and EDCI in an organic solvent for reflux reaction (50-80°C), and the mixture was obtained after purification;
[0019] S2. Preparation of DBM: removing blood and adipose tissue from bones of non-human mammals, acid-decalcifying, decellularizing, enzymatically removing collagen telopeptides, and spray-drying to obtain DBM;
[0020] S3. Preparation of PEG-GA-COO-NHS encapsulated liposomes: liposomes were prepared by thin film evaporation method, PEG-GA-COO-NHS was added thereto, hydrated, purified and spray-dried to obtain liposomes.
[0021] The third aspect of the present invention provides the use of the modified hydroxyapatite bone repair material in the preparation of a bone defect treatment product.
[0022] A fourth aspect of the present invention provides a bone defect treatment product, the bone defect treatment product at least comprising the above-mentioned modified hydroxyapatite bone repair material;
[0023] Furthermore, the bone defect treatment product comprises a solid phase material and a liquid phase material, the solid phase material is the above-mentioned modified hydroxyapatite bone repair material, and the liquid phase material can be water.
[0024] The bone defect treatment product may be a medical device, specifically an implantable medical device.
[0025] Beneficial technical effects of one or more of the above technical solutions:
[0026] (1) Hydroxyapatite modified with COOH-PEG-COOH has high strength, high toughness and good biocompatibility;
[0027] (2) Demineralized bone matrix powder is used to increase the compressive strength of the material, and immediately cross-links with NHS-PEG-COO-HA through chemical bonds to prevent the collapse of hydroxyapatite after injection into the tissue, thereby guiding the body's bone tissue regeneration;
[0028] (3) PEG-GA-COO-NHS liposomes are used as sustained-release crosslinking agents. After the modified hydroxyapatite is injected into the defective tissue, PEG-GA-COO-NHS is slowly released from the liposomes and chemically crosslinked with the defective tissue, NHS-PEG-COO-HA, and DBM. This not only increases the further crosslinking of the material's own components, but also promotes the combination of the material and the defective tissue, further preventing the late collapse and facilitating the repair of the defective tissue.
[0029] (4) It is injectable and the curing time can be controlled by adjusting the proportion of each component. The clinical operation is simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0031] Figure 1 This is the H-NMR spectrum of COOH-PEG20K-COOH prepared in Example 1 of the present invention.
[0032] Figure 2 This is the hydrogen NMR spectrum of PEG8K-GA prepared in Example 1 of the present invention.
[0033] Figure 3 This is the H NMR spectrum of PEG8K-GA-COO-NHS prepared in Example 1 of the present invention.
[0034] Figure 4 This is the infrared analysis graph of the modified hydroxyapatite prepared in Example 1 of the present invention; wherein, curve A represents hydroxyapatite (HA); curve B represents COOH-PEG-COOH, and curve C represents NHS-PEG-COO-HA.
[0035] Figure 5 This is a schematic diagram of the structure of the bone repair material prepared in Example 1 of the present invention.
[0036] Figure 6 This is the antibacterial graph of the bone repair material prepared in Example 1 of the present invention.
[0037] Figure 7 This is the osteogenic gene expression of the bone repair material prepared in Example 1 of the present invention; wherein A is 7d and B is 14d.
[0038] Figure 8 This is the HE staining picture of in vivo bone repair of the bone repair material prepared in Example 1 of the present invention; wherein A is Example 1, B is Example 3, and C is Comparative Example 1.
[0039] Fig. 9 This is a diagram showing the injection performance of the modified hydroxyapatite bone repair material prepared in Example 1 of the present invention.
[0040] Fig.10 This is a graph showing the anti-collapse performance of the modified hydroxyapatite bone repair material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0041] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0042] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components and / or combinations thereof. It should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention.
[0043] As mentioned above, injectable bone cement is often used in the treatment of bone defects, but it has many problems such as potential toxicity, non-degradability and lack of biological activity, long curing time, poor injectability, and poor anti-collapse property.
[0044] In view of this, the present invention provides a modified hydroxyapatite bone repair material, wherein the modified hydroxyapatite bone repair material comprises at least the following raw materials in parts by weight:
[0045] NHS-PEG-COO-HA 5-15 parts, DBM 0.5-3 parts, PEG-GA-COO-NHS-encapsulated liposomes 0.1-1 parts;
[0046] Wherein, the structural formula of the NHS-PEG-COO-HA is:
[0047] n can be 300 to 1200.
[0048] The DBM is prepared by a method comprising: defatting, decalcifying, decellularizing, and removing telopeptide from bones of non-human animals, and drying the bones to obtain the DBM.
[0049] Among them, the structural formula of PEG-GA-COO-NHS is:
[0050]
[0051] n can be 100-400.
[0052] The modified hydroxyapatite bone repair material is a gel preparation, which can be solidified by adding water (such as saline) to obtain a modified hydroxyapatite bone repair material. The mass volume ratio of solid (i.e., modified hydroxyapatite bone repair material) to liquid (i.e., water) is 1-5:0.5-3 (g / mL), preferably 3:2.
[0053] In another specific embodiment of the present invention, a method for preparing the modified hydroxyapatite bone repair material is provided, the preparation method comprising:
[0054] S1. Preparation of NHS-PEG-COO-HA: COOH-PEG-COOH modified hydroxyapatite (COOH-PEG-HA) was dissolved with NHS and EDCI in an organic solvent for reflux reaction (50-80°C), and the mixture was obtained after purification;
[0055] S2. Preparation of DBM: removing blood and adipose tissue from bones of non-human mammals, acid-decalcifying, decellularizing, enzymatically removing collagen telopeptides, and spray-drying to obtain DBM;
[0056] S3. Preparation of PEG-GA-COO-NHS encapsulated liposomes: liposomes were prepared by thin film evaporation method, PEG-GA-COO-NHS was added thereto, hydrated, purified and spray-dried to obtain liposomes.
[0057] It should be noted that there is no particular order for steps S1, S2 and S3.
[0058] Wherein, the synthesis route of NHS-PEG-COO-HA in step S1 is as follows:
[0059]
[0060] Further, the synthesis route of the COOH-PEG-HA is as follows:
[0061]
[0062] Furthermore, the synthesis route of COOH-PEG-COOH is as follows:
[0063]
[0064] The molecular weight of polyethylene glycol PEG is 10-30K, and more preferably 20K.
[0065] In step S2, the non-human mammal can be a pig, dog, cow, sheep, etc., preferably a pig; the bone can be a femur. Furthermore, the preparation method comprises: cutting the pig femur, washing with water to remove blood and adipose tissue, decalcifying with a saline hydrochloric acid solution for 80-100 hours, then treating with 1-5 mol / L NaOH for 1-5 hours, 0.05-1 mol / LEDTA-2Na for 10-40 hours, and 0.1-1 mol / L HCl to obtain demineralized matrix bone; the demineralized matrix bone is mixed with pepsin (enzyme activity 10-1000 U / g) at a mass ratio of 10-100:1, and then added into 0.05-1 mol / L HCl for enzymatic hydrolysis for 1-5 days; adjusting the pH to 6.5-7.0 until collagen precipitates and removes the terminal peptide, stirring and separating to obtain a precipitate, and the precipitate is dissolved in water and spray-dried to obtain the precipitate.
[0066] The synthesis route of PEG-GA-COO-NHS in step S3 is as follows:
[0067]
[0068] Among them, PEG-GA-COOH, its synthesis route is as follows:
[0069]
[0070] Among them, polyethylene glycol-modified gallic acid has the following synthesis route:
[0071]
[0072] The molecular weight of polyethylene glycol PEG is 5K-10K, and more preferably 8K.
[0073] In the thin film evaporation method for preparing liposomes, the membrane material of the liposomes can be soybean lecithin and cholesterol, and the mass ratio of the two is 1:0.05-0.5, preferably 1:0.2; the specific conditions of the hydration reaction are: reacting at 30-50°C (preferably 40°C) for 0.2-2h (preferably 1h).
[0074] In another specific embodiment of the present invention, the preparation method further comprises the step of mixing the raw materials obtained in steps S1-S3.
[0075] In another specific embodiment of the present invention, there is provided a use of the modified hydroxyapatite bone repair material in the preparation of a bone defect treatment product.
[0076] In another specific embodiment of the present invention, a bone defect treatment product is provided, wherein the bone defect treatment product at least comprises the above-mentioned modified hydroxyapatite bone repair material;
[0077] Furthermore, the bone defect treatment product comprises a solid phase material and a liquid phase material, wherein the solid phase material is the modified hydroxyapatite bone repair material, and the liquid phase material can be water, preferably physiological saline, and the solid-liquid mass volume ratio of the two is 1-5:0.5-3 (g / mL), preferably 3:2.
[0078] When used, the solid phase material and the liquid phase material are mixed to form a hydrogel preparation for repairing and treating bone defects.
[0079] The bone defect treatment product may be a medical device, specifically an implantable medical device.
[0080] In the present invention, the bone defect treatment product has multiple functions such as injectability, adjustable solidification time, anti-collapse, compressive strength, anti-infection, good biocompatibility and guiding bone tissue regeneration.
[0081] The present invention is further explained by the following examples, but they are not intended to limit the present invention. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0082] Example 1
[0083] 1. Preparation of NHS-PEG20K-COO-HA
[0084] (1) Preparation of COOH-PEG20K-COOH: 100 g PEG (20K) and 1.77 g succinic anhydride were weighed and dissolved in 1000 mL dichloromethane (CH2Cl2), 86 mg p-toluenesulfonic acid was added, and the mixture was refluxed at 60°C for 7 h, cooled to room temperature, washed twice with water, shaken to separate the layers, and the lower layer was collected. After rotary evaporation until the flask had a constant weight, the mixture was vacuum dried at 40°C to obtain a white waxy solid COOH-PEG20K-COOH. The reaction process and reaction products were quality controlled by measuring the number of carboxyl groups.
[0085]
[0086] like Figure 1 In the H NMR spectrum, the chemical shift at 0 is the internal standard TMS. The peak at 7.39 is the deuterated chloroform solvent peak. The three peaks at 3.51-3.79 are the peaks on the PEG chain. H14 at 2.63 and H16 at 4.24 are both triple peaks, which are the two CH2 peaks of the introduced succinic acid. It can be calculated that the degree of substitution of succinic anhydride is 100%.
[0087] (2) COOH-PEG20K-COOH modified hydroxyapatite: 100 g COOH-PEG20K-COOH was weighed and dissolved in 1000 mL of a mixed solution of CH2Cl2 and acetone (the volume ratio of CH2Cl2 and acetone was 5:1), 86 mg of sodium p-toluenesulfonate was added, 1.26 g of hydroxyapatite (Ca5(PO4)3OH, HA) (less than 0.2 mm) was dispersed in the above solution, and reacted at 60°C for 7 h; dialyzed with water for 48 h, vacuum dried, placed in a vacuum drying oven, and dried at 50°C for 6 h to obtain COOH-PEG20K-HA with a yield of 83%.
[0088]
[0089] (3) NHS-PEG20K-COO-HA: 100 g COOH-PEG20K-HA, 1.15 g NHS, and 1.92 g 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCI) were weighed and dissolved in 1000 mL CH2Cl2. The mixture was refluxed for 8 h. The reaction solution was filtered and the residue was washed three times with CH2Cl2. The product was a white solid. The solid was dried under vacuum at 40°C for more than 12 h to obtain NHS-PEG20K-COO-HA.
[0090]
[0091] 2. Preparation of DBM dry powder
[0092] The pig femur was cut into about 15mm×15mm, washed with water to remove blood and fat tissue, decalcified with hydrochloric acid decalcification solution (15mL concentrated hydrochloric acid, 7.5g NaCl, distilled water to 100mL) for 96h, 2mol / L NaOH for 2h, 0.5mol / L EDTA-2Na for 24h, 0.5mol / L HCl for 30min, and then replaced with a new hydrochloric acid solution for 3 times; demineralized matrix bone was obtained. The mass ratio of matrix to pepsin was 50:1, the activity of pepsin was 170U / g, the final concentration of matrix was 1%, dissolved in 0.1mol / L HCl, and enzymolyzed at 25℃ for 72h; the pH was adjusted to 6.5-7.0 until collagen precipitated, the telopeptide was removed, stirring was continued for 24h, centrifuged at 12000rpm for 30min, the supernatant was discarded, the precipitate was dissolved in purified water, and spray dried to obtain DBM dry powder.
[0093] 3. Preparation of PEG-GA-COO-NHS
[0094] (1) Weigh 40 g PEG8K and 5.1 g GA and dissolve them in 400 mL CH2Cl2. Slowly add 86 mg p-toluenesulfonic acid and reflux at 90°C for 6 h. After the reaction, remove the precipitate using a separatory funnel. Remove the organic solvent by rotary evaporation and dialyze with water for 48 h. Freeze-dry to obtain polyethylene glycol 8K-modified gallic acid (PEG8K-GA).
[0095]
[0096] The results are as follows Figure 2 In the H NMR spectrum, the chemical shift at 0 is the internal standard TMS, and the peak at 7.39 is the deuterated chloroform solvent peak.
[0097] The three peaks at 3.51-3.79 are the peaks on the PEG chain, and the single peak at 7.18 is the two CH peaks of the introduced gallic acid. Figure 2 It can be calculated that the reaction of PEG8K is complete and the degree of substitution of gallic acid is 37%.
[0098] (2) Weigh 40 g of freeze-dried PEG8K-GA and 5.90 g of succinic anhydride and dissolve them in 400 mL of CH2Cl2, add 86 mg of p-toluenesulfonic acid, and reflux at 60°C for 6 h. After the reaction, separate and purify with 0.1 mol / L hydrochloric acid, remove the organic solvent by rotary evaporation, and dialyze with water for 48 h; freeze-dry to obtain PEG8K-GA-COOH.
[0099]
[0100] (3) Weigh 40 g of PEG8K-GA-COOH, 5.75 g of NHS, and 11.50 g of EDCI and dissolve them in 400 mL of CH2Cl2. Reflux for 6 h. Filter the reaction solution to remove the residue. The filtrate is colorless. Rotary evaporate the filtrate and vacuum dry it at 40°C for more than 12 h to obtain PEG-GA-COO-NHS. Figure 3 As shown in the H NMR spectrum, the hydroxyl groups of PEG8K-GA-COOH were connected with succinic acid groups and NHS groups to obtain PEG8K-GA-COO-NHS.
[0101]
[0102] 4. Preparation of PEG8K-GA-COO-NHS Liposomes
[0103] Liposomes were prepared by thin film evaporation. Accurately weigh 2g of soybean lecithin and 0.4g of cholesterol, add 100mL of anhydrous ethanol, ultrasonicate for 10min to dissolve, transfer to a round-bottom flask, and evaporate under reduced pressure at 40°C on a rotary evaporator for 40min to remove anhydrous ethanol and form a uniform lipid film. Add 10mL of 20% PEG8K-GA-COO-NHS and 10mL of 1% Tween-80 to the round-bottom flask, rotate and hydrate (hydration temperature 40°C) for 1h until the film is completely detached to form a milky white suspension, and ultrasonicate for 10min (power 60W). The obtained PEG8K-GA-COO-NHS-encapsulated liposomes were filtered through a 0.45μm aqueous microporous filter membrane and spray dried to obtain the PEG8K-GA-COO-NHS-encapsulated liposome dry powder.
[0104] 5. Preparation of modified hydroxyapatite bone repair materials
[0105] Add 1.5 g of PEG8K-GA-COO-NHS liposome freeze-dried powder, 3 g of DBM dry powder, and 25.5 g of NHS-PEG20K-COO-HA to 20 mL of normal saline and stir to form a modified hydroxyapatite bone repair material. The composition analysis results are as follows: Figure 4 , from top to bottom: infrared spectra of HAP, HOOC-PEG20K-COOH, and NHS-PEG20K-COO-HA. Figure 4 It shows that the modified natural nano-hydroxyphosphite was successfully grafted, with infrared peaks corresponding to the orthophosphate in HAP (purple frame) and -CH2 in PEG (green frame), as well as the infrared peak of the newly formed ester bond in NHS-PEG20K-COO-HA (blue frame). Fig. 9 It has shown excellent injectability and can be used in minimally invasive surgery. Fig.10 Has good anti-collapse performance.
[0106] Comparative Example 1
[0107] Purchase commercially available CPC materials.
[0108] Comparative Example 2
[0109] NHS-PEG20K-COO-HA, DBM dry powder, and PEG-GA-COO-NHS were directly mixed in proportion, with a coagulation time of 2 minutes. The coagulation was fast and could not be used in surgery.
[0110] Comparative Example 3
[0111] Except for not adding DBM dry powder, the other steps are the same as Example 1.
[0112] Effect verification
[0113] 1. Cytotoxicity assay
[0114] The CCK-8 method was used to evaluate the in vitro cytotoxicity of the bone repair material prepared by the present invention. The samples of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were coated on a 96-well cell culture plate, inoculated with L929 cells, with an inoculation density of about 1000 cells / well, and 5 parallel wells were set. At the same time, a DMEM medium without cells was used as a blank control group. After culturing in an incubator (37°C, 5% CO2) for 48 hours, 10 μL of CCK-8 solution was added to each well, and after continuing to incubate in a 37°C incubator for 4 hours, 80 μL of liquid was drawn and added to a new 96-well plate, and the absorbance value was detected at a wavelength of 450 nm using an ELISA instrument to calculate the cell viability.
[0115] As can be seen from Table 1, the cell viability is above 100%, the toxicity level is 0, and the biocompatibility is excellent.
[0116] Table 1 Cytotoxicity of materials in each group
[0117]
[0118]
[0119] 2. Compressive strength analysis
[0120] After curing the cylindrical samples prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 at 37°C and 100% humidity for 30 minutes, they were placed in simulated body fluid for further hydration for 6 hours / 12 hours / 24 hours / 36 days. The samples were taken out, rinsed with deionized water, and the residual surface moisture was absorbed with filter paper, and then placed in a 60°C oven for drying. Afterwards, the two ends of the dried samples were smoothed with sandpaper, and the compressive strength test was performed on a universal testing machine. The range of the universal testing machine was 5kN, and the loading rate was 1mm / min. The maximum load Fmax was recorded.
[0121] σ=4Fmax / πd 2
[0122] Wherein σ is compressive strength (MPa), Fmax is maximum compressive load (N), and d is sample diameter (mm). As shown in Table 2, Example 1 reaches a maximum compressive strength of 38.43 MPa in 24 hours, the compressive strength of Comparative Example 1 is 19.37 MPa, Comparative Example 2, the group without liposome sustained release, reaches a maximum compressive strength of 37.21 MPa after immersion for 12 hours, has a short coagulation time, and reaches the maximum mechanical properties first, and Comparative Example 3 has a maximum compressive strength of 28.45 MPa.
[0123] Table 2 Mechanical properties of each group of materials at different stages
[0124] Solidification 6h 12h 24h 48h Example 1 (MPa) 17.18 25.34 38.43 35.39 Comparative Example 1 (MPa) 14.36 18.69 19.37 16.75 Comparative Example 2 (MPa) 29.57 37.21 36.11 35.42 Comparative Example 3 (MPa) 15.29 22.46 28.45 24.33
[0125] 3. Evaluation of curing time performance
[0126] The curing time is in accordance with the standard ASTM C191-13, and the setting time of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 is measured using a Gilmore apparatus, as shown in Table 3.
[0127] Table 3 Evaluation of material curing time
[0128] Solidification Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Initial setting time (min) 15 9 2 13 Final setting time (min) 45 21 8 38
[0129] 4. Evaluation of anti-infection performance
[0130] The bone repair material prepared in Example 1 was made into discs, and Escherichia coli was selected to conduct an antibacterial experiment. Figure 6 An obvious inhibition zone appeared around the material, indicating that the antibacterial bone repair material had good antibacterial properties against Escherichia coli.
[0131] 5. Evaluation of in vitro osteogenic performance
[0132] (1) The bone repair materials prepared in Example 1 and Comparative Example 1 were placed in 6-well plates respectively. 2 mL of culture medium was added to the wells of the experimental group so that the materials were close to the bottom of the wells and there was a small amount of liquid on the materials. 1 mL of culture medium was added to the wells of the control group and the blank control group and shaken to spread the culture medium evenly on the bottom of the wells.
[0133] (2) Add 0.5 mL of 1×10 5 / mL cell suspension (5×10 4 cells / well), add the cell suspension from the top of the well near the middle of the liquid surface, shake it slightly up and down and left and right to evenly distribute the cells, let it stand on a horizontal table for 10 minutes, and then move it to the incubator.
[0134] The design groups are as follows, with 3 parallels in each group.
[0135] Experimental group: MG63 cells were inoculated on the bone repair materials prepared in Example 1 and Comparative Example 1, and the differentiation of MG63 cells was induced by using the induction solution.
[0136] Control group: MG63 cells were inoculated in the wells of the plate and induced to differentiate using the induction solution.
[0137] (3) RT-qPCR test
[0138] On days 7 and 14, the expression of osteogenic-related genes was detected by RT-qPCR. According to the instructions of the RNA rapid extraction kit, RNA was extracted through lysis, column loading, column washing and elution steps. Subsequently, the RNA was reverse transcribed into cDNA using a reverse transcription kit. The cDNA obtained by reverse transcription was used as a template to detect the expression of osteogenic differentiation-related genes (ALP, Runx2, OCN). GAPDH was set as the internal reference gene, and the 2-ΔΔct method was used to calculate the relative expression of mRNA. The primer sequences are shown in Table 4. The expression levels of related genes are shown in Table 4. Figure 7 The expression of osteoblast-related genes ALP, Runx2, and OCN was upregulated in vitro by Example 1 and Comparative Example 1. The upregulation ratio of osteoblast-related genes in Example 1 was higher than that in Comparative Example 1, which was significantly different from that in the control group. This indicates that the bone repair material prepared in Example 1 can effectively regulate the differentiation of osteoblasts and promote bone repair.
[0139] Table 4 Primer design
[0140] Gene Upstream primer (5′-3′) Downstream primer (3′-5′) ALP AACATCAGGGACATTGACGTG(SEQ ID NO.1) GTATCTCGGTTTGAAGCTCTTCC(SEQ ID NO.2) OCN GGCGCTACCTGTATCAATGG(SEQ ID NO.3) GTGGTCAGCCAACTCGTCA(SEQ ID NO.4) <![CDATA[Runx2]]> CCGCCTCAGTGATTTAGGGC(SEQ ID NO.5) GGGTCTGTAATCTGACTCTGTCC(SEQ ID NO.6)
[0141] 6. Evaluation of in vivo osteogenic performance
[0142] Experimental study on repairing mandibular defect in rabbits
[0143] Methods: Fast for 4 hours before surgery, inject 20% urethane (prepared with saline, anesthetic dose: 4mL / kg) into the ear vein, fix the patient on the operating table after anesthesia, wipe and disinfect with alcohol, make a notch (13mm×6mm) in the mandible, add the material prepared in Example 1 to the defect, and set up a control group, add the commercially available CPC material of Comparative Example 1 and the material prepared in Comparative Example 3 to the defect, drip gentamicin sulfate to prevent infection, then suture the wound and disinfect with iodine tincture. The patient can be fed and given water after waking up. Sodium penicillin is injected intramuscularly continuously for three days after surgery to prevent infection. The patient was killed 4 weeks after surgery to observe the repair condition, and the bone filling site was observed by pathological sections. The results are as follows Figure 8 : Example 1 has a large amount of new bone formation (A△); Comparative Example 3 has a large amount of fibroblasts filling the bone defect (B◇), with a small amount of new bone formation (B△); Comparative Example 1 has a large amount of fibroblasts filling the bone defect (C◇). The new bone formation in Example 1 group is significantly greater than that in each control group.
[0144] It should be noted that the above examples are only used to illustrate the technical solution of the present embodiment and are not intended to limit it. Although the present embodiment is described in detail with reference to the given examples, a person of ordinary skill in the art may modify or replace the technical solution of the present embodiment as required without departing from the spirit and scope of the technical solution of the present embodiment.
Claims
1. A modified hydroxyapatite bone repair material, characterized in that: The modified hydroxyapatite bone repair material comprises at least the following raw materials in parts by weight: NHS-PEG-COO-HA 5-15 parts, DBM 0.5-3 parts, PEG-GA-COO-NHS-encapsulated liposomes 0.1-1 parts; Wherein, the structural formula of the NHS-PEG-COO-HA is: n is 300 to 1200; The DBM is prepared by a method comprising: degreasing, decalcifying, decellularizing, and de-telopeptidizing the bones of non-human animals, and drying them to obtain the DBM; Among them, the structural formula of PEG-GA-COO-NHS is: n is 100 to 400.
2. The method for preparing the modified hydroxyapatite bone repair material according to claim 1, characterized in that: The preparation method comprises: S1. Preparation of NHS-PEG-COO-HA: COOH-PEG-COOH modified hydroxyapatite (COOH-PEG-HA) was dissolved with NHS and EDCI in an organic solvent for reflux reaction (50-80°C), and the mixture was obtained after purification; S2. Preparation of DBM: removing blood and adipose tissue from bones of non-human mammals, acid-decalcifying, decellularizing, enzymatically removing collagen telopeptides, and spray-drying to obtain DBM; S3, preparation of PEG-GA-COO-NHS encapsulated liposomes: liposomes were prepared by thin film evaporation method, PEG-GA-COO-NHS was added thereto, hydrated, purified and spray-dried to obtain; There is no particular order in which steps S1, S2 and S3 are performed.
3. The preparation method according to claim 2, characterized in that: The synthesis route of NHS-PEG-COO-HA in step S1 is as follows:
4. The preparation method according to claim 3, characterized in that: The synthetic route of COOH-PEG-HA is as follows: Furthermore, the synthesis route of COOH-PEG-COOH is as follows: The molecular weight of polyethylene glycol PEG is 10-30K, and further 20K.
5. The preparation method according to claim 2, characterized in that: In step S2, the non-human mammal is a pig, and the bone is a femur.
6. The preparation method according to claim 2, characterized in that: In the step S2, the preparation method comprises: cutting the pig femur, washing with water to remove blood and adipose tissue, decalcifying with a saline hydrochloric acid solution for 80-100 hours, then treating with 1-5 mol / L NaOH for 1-5 hours, 0.05-1 mol / L EDTA-2Na for 10-40 hours, and 0.1-1 mol / L HCl to obtain demineralized matrix bone; mixing the demineralized matrix bone with pepsin (enzyme activity 10-1000 U / g) at a mass ratio of 10-100:1, adding the mixture into 0.05-1 mol / L HCl for enzymatic hydrolysis for 1-5 days; adjusting the pH to 6.5-7.0 until collagen precipitates and removes the terminal peptide, stirring and separating to obtain a precipitate, dissolving the precipitate with water, and spray drying.
7. The preparation method according to claim 2, characterized in that: The synthesis route of PEG-GA-COO-NHS in step S3 is as follows: Further, PEG-GA-COOH, its synthesis route is as follows: Further, polyethylene glycol-modified gallic acid has the following synthesis route: The molecular weight of polyethylene glycol PEG is 5K-10K, and more preferably 8K.
8. The preparation method according to claim 2, characterized in that: In the thin film evaporation method for preparing liposomes, the membrane materials of the liposomes are soybean lecithin and cholesterol, and the mass ratio of the two is 1:0.05-0.5, preferably 1:0.2; the specific conditions of the hydration reaction are: reacting at 30-50° C. for 0.2-2h.
9. Use of the modified hydroxyapatite bone repair material according to claim 1 or the modified hydroxyapatite bone repair material prepared by the preparation method according to any one of claims 2 to 8 in preparing a product for treating bone defects.
10. A bone defect treatment product, characterized in that: The bone defect treatment product is at least the modified hydroxyapatite bone repair material according to claim 1 or the modified hydroxyapatite bone repair material prepared by the preparation method according to any one of claims 2 to 8; Furthermore, the bone defect treatment product comprises a solid phase material and a liquid phase material, wherein the solid phase material is the modified hydroxyapatite bone repair material, and the liquid phase material is water, further physiological saline; the solid-liquid mass volume ratio of the two is 1-5:0.5-3 (g / mL); Furthermore, the bone defect treatment product is a medical device, specifically an implantable medical device.